The Concept of a Greenhouse with Intelligent Microclimate Control and Near-Zero Energy Consumption: Renewable Energy, Accumulation, and Designed Thermal Balance - Sherobod Khudaykulov Berdimurod ugli; Islomnur Ibragimov; Botirov Feruz Begmurod ugli; Choriev Zafarbek Mahmud ugli; Karimov Diyyorbek Toshtemir ugli; Mukhammadiyev Akbarali Lukmon ugli (Genius Journals, 2025)
This article presents a scientific and applied concept of a new generation greenhouse with intelligent microclimate control (Smart Greenhouse AI) and near-zero energy consumption (Near-Zero-Energy Greenhouse, NZEG). The main focus is on the integration of renewable energy sources – solar, geothermal, and wind – with heat storage systems and artificial intelligence for adaptive control of heat flows. The use of predictive algorithms based on neural networks and a digital twin of the microclimate allows for stabilizing temperature and humidity with minimal energy costs. Simulation results in MATLAB Simulink show that the application of AI control reduces electricity consumption by 35–45%, reduces temperature deviations by 70%, and increases resistance to external disturbances. The proposed concept defines the engineering foundations of future greenhouses that comply with the principles of sustainable agriculture and "smart" energy systems.
Keywords: Intelligent greenhouse; greenhouse microclimate; renewable energy sources